Kuwait : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that economic activity in Kuwait picked up in 2014. Non-oil growth is projected at 3.5 percent driven by a combination of continued increase in domestic consumption and some pick-up in government capital spending and private investment. Flat oil production would keep the overall real GDP growth positive at 1.3 percent. The average inflation rate is forecast to remain at about 3 percent. The current account and fiscal surpluses are expected to remain high. The medium-term economic outlook is favorable. Non-oil GDP growth is expected to pick up to 4 to 5 percent in the medium term, supported by government investment in infrastructure and the oil sector, and by consumption.